A bibliometric analysis of solar power research from 1991 to 2010 - Dong, Bensi; Xu, Guoqiang; Luo, Xiang; Cai, Yi; Gao, Wei (Scientometrics, 2012)
A bibliometric analysis was performed on solar power-related research between 1991 and 2010 in journals of all the subject categories of the Science Citation Index. “Solar cell”, “solar energy”, “solar power”, “solar radiation” and “solar thermal” were selected as keywords to search in a part of the title, abstract or keywords. The trends were analyzed with the retrieved results in the publication type and language, characters of scientific output, publication distribution by countries, subject categories and journals, and the frequency of title-words and keywords used. Articles on solar power showed a significant growth along with more participation of countries, while the percentage of international papers reduced. The USA was the country with the most related articles and the most-frequent partner among all the international collaborative articles. Articles of Mainland China and South Korea grew much faster than other countries in the latest 5 years. Chemistry and material fields gradually became the mainstream of the solar power research. Synthetically analyzing three kinds of keywords, it showed that thin film solar photovoltaic technology was a hot spot of the solar power research in the past 20 years. “Dye-sensitized solar cell” and “organic” had extremely high increasing rates, which indicated that more attention was paid to kinds of organic solar cells. It could be concluded that the materials of solar cells would be the emphasis of solar power research in the twenty-first century.